Kinerja Keuangan Pemerintah Daerah Kota Bogor Tahun 2011-2020 - Rea Dwiardhya Garini; Faizal Maad; James Sinurat (BINA: JURNAL PEMBANGUNAN DAERAH, 2023)
ABSTRACTThis study aims to determine the Financial Performance of the Regional Government of Bogor City in 2011-2020 in terms of financial ratios and the factors that affect the Financial Performance of the Regional Government of Bogor City in 2011-2020. This research is a type of quantitative descriptive research carried out in the ranks of the Bogor City Government, West Java Province. The data in this study are secondary data obtained from the Central Bureau of Statistics of the City of Bogor. The data analysis method used is ratio analysis and descriptive analysis, multiple linear regression analysis, classical assumption test and hypothesis testing. The results of the financial performance analysis, in terms of the ratios: (1) Regional Financial Independence Ratio in the category of Medium regional ability, and Participatory relationship patterns. (2) Regional Financial Dependency Ratio with Very High category. (3) The Degree Ratio of Regional Financial Fiscal Decentralization in the Enoughcategory. (4) Effectiveness Ratio to Regional Original Revenue with Very Effective criteria. (5) Regional Financial Efficiency Ratio with Inefficient criteria.The results of the analysis in terms of the factors that affect the financial performance of the region. The Regional Original Income variable partially has a significant positive effect on the Financial Performance of the Regional Government of the City of Bogor. The Balancing Fund partially has a significant negative effect on the Financial Performance of the Regional Government of Bogor City. The variables of Local Original Income and Balanced Funds simultaneously have a significant effect on the Financial Performance of the Regional Government of Bogor City. (Times New Roman, 10Pts, Italic, Spacing: Single space)Keywords: Regional Financial Performance, Financial Ratios, APBD. ABSTRAKPenelitian ini bertujuan untuk mengetahui Kinerja Keuangan Pemerintah Daerah Kota Bogor Tahun 2011-2020 ditinjau dari rasio keuangan dan faktor-faktor yang mempengaruhi Kinerja Keuangan Pemerintah Daerah Kota Bogor tahun 2011-2020. Penelitian ini merupakan jenis penelitian deskriptif kuantitatif yang dilaksanakan di jajaran Pemerintah Kota Bogor Provinsi Jawa Barat. Data dalam penelitian ini merupakan data sekunder yang diperoleh dari Badan Pusat Statistik Kota Bogor. Metode analisis data yang digunakan adalah analisis rasio dan analisis deskriptif, analisis regresi linier berganda, uji asumsi klasik serta pengujian hipotesis. Hasil analisis kinerja keuangan, ditinjau dari rasio: (1) Rasio Kemandirian Keuangan Daerah dalam kategori kemampuan daerah Sedang, dan pola hubungan Partisipatif. (2) Rasio Ketergantungan Keuangan Daerah dengan kategori Sangat Tinggi. (3) Rasio Derajat Desentralisasi Fiskal Keuangan Daerah dengan kategori Cukup. (4) Rasio Efektifitas terhadap Pendapatan Asli Daerah dengan kriteria Sangat Efektif. (5) Rasio Efisiensi Keuangan Daerah dengan kriteria Tidak Efisien. Hasil analisis ditinjau dari faktor-faktor yang mempengaruhi kinerja keuangan daerah. Variabel Pendapatan Asli Daerah secara parsial berpengaruh positif signifikan terhadap Kinerja Keuangan Pemerintah Daerah Kota Bogor. Dana Perimbangan secara parsial berpengaruh negatif signifikan terhadap Kinerja Keuangan Pemerintah Daerah Kota Bogor. Variabel Pendapatan Asli Daerah dan Dana Perimbangan secara simultan berpengaruh signifikan terhadap Kinerja Keuangan Pemerintah Daerah Kota Bogor.Kata Kunci: Kinerja Keuangan Daerah, Rasio Keuangan, APBD.